Simulated Variation Characteristics of Oceanic CO2 Uptake, Surface Temperature, and Acidification in Zhejiang Province, China - Wang, Kuo; Zhang, Han; Fan, Gao-Feng; Li, Zheng-Quan; Yu, Zhen-Yan; Liu, Pei-Pei (Frontiers in Physics, 2021)
Since pre-industrial times, atmospheric CO2 content increased continuously, leading to global warming through greenhouse effect. Ocean carbon sequestration mitigates global warming; on the other hand, oceanic CO2 uptake would reduce seawater pH, which is termed ocean acidification. We perform Earth system model simulations to assess ocean CO2 uptake, surface temperature and acidification for Zhejiang offshore, one of the most vulnerable areas to marine disasters. In the last 40 years, atmospheric CO2 concentration increased by 71 ppm, and sea surface temperature (SST) in Zhejiang offshore rose at a rate of 0.16℃/10a. Cumulative ocean CO2 uptake in Zhejiang offshore is 0.3 PgC, resulting in an increase of 20% in sea surface hydrogen ion concentration, and the acidification rate becomes faster in the last decade. 2020-2040, under four RCP scenarios, SST in Zhejiang offshore increases by 0.3-0.5 ℃, whereas cumulative ocean carbon sequestration is 0.150-0.165 PgC. Relative to RCP2.6, the decrease of surface pH in Zhejiang offshore is doubled under RCP8.5. Furthermore, simulated results show that the relationship between CO2 scenario and ocean carbon cycle is nonlinear, which hints that deeper reduction of anthropogenic CO2 emission may be needed if we aim to mitigate ocean acidification in Zhejiang offshore under a higher CO2 concentration scenario. Our study quantifies the change characteristics of ocean climate and carbon cycle fields in Zhejiang offshore, and provide new insight into the responses of ocean carbon cycle and climate system to oceanic carbon sequestration.